2019
DOI: 10.1016/j.phymed.2019.152905
|View full text |Cite
|
Sign up to set email alerts
|

Updated insights into the mechanism of action and clinical profile of the immunoadjuvant QS-21: A review

Abstract: Background: Vaccine adjuvants are compounds that significantly enhance/prolong the immune response to a coadministered antigen. The limitations of the use of aluminium salts that are unable to elicite cell responses against intracellular pathogens such as those causing malaria, tuberculosis, or AIDS, have driven the development of new alternative adjuvants such as QS-21, a triterpene saponin purified from Quillaja saponaria. Purpose: The aim of this review is to attempt to clarify the mechanism of action of QS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(132 citation statements)
references
References 70 publications
2
106
0
2
Order By: Relevance
“…Whist the molecular mechanisms underlying the adjuvant effect of QS-21 are not yet fully understood, it has been demonstrated that it induces strong and persistent Th2 humoral and Th1 cell-mediated immune responses ( 105 ). It is thought that the use of liposomal formulations facilitates the escape of the antigen into the cytosol enhancing antigen-presentation through MHC-I pathway leading to cross-presentation to CD8 + T cells and an early IFN-gamma response that promotes vaccine immunogenicity ( 106 ). Interestingly, the AS01B adjuvant system seems to require the synergistic action of the three components together for optimal adjuvant effect ( 107 ).…”
Section: Current Strategies To Improve Vaccine Effectivenessmentioning
confidence: 99%
“…Whist the molecular mechanisms underlying the adjuvant effect of QS-21 are not yet fully understood, it has been demonstrated that it induces strong and persistent Th2 humoral and Th1 cell-mediated immune responses ( 105 ). It is thought that the use of liposomal formulations facilitates the escape of the antigen into the cytosol enhancing antigen-presentation through MHC-I pathway leading to cross-presentation to CD8 + T cells and an early IFN-gamma response that promotes vaccine immunogenicity ( 106 ). Interestingly, the AS01B adjuvant system seems to require the synergistic action of the three components together for optimal adjuvant effect ( 107 ).…”
Section: Current Strategies To Improve Vaccine Effectivenessmentioning
confidence: 99%
“…They were used in more than 100 human clinical trials [70,71] where they demonstrated the ability to induce humoral and cell-mediated immune response against a wide range of antigens [72]. Also, the QS-21 fraction was superior to aluminum salts because they induced a Th1-type immune response, which is essential for controlling intracellular pathogens [73].…”
Section: Saponinsmentioning
confidence: 99%
“…Additionally MPL is a TLR-4 receptor agonist, which stimulates helper T cells to produce interferon-γ (IFN-γ) and induces plasma cells to express IgG2a antibodies (30). QS-21, a saponin extracted from Q. saponaria tree bark, promotes antigen-specific antibody responses and CD8+ T-cell responses in mice (31). Besides squalene-based adjuvants, chitosan has also attracted attention as a vaccine adjuvant.…”
Section: Introductionmentioning
confidence: 99%